On recent advances in the Beltrami equations - Gutlyanskii, V.; Ryazanov, V.; Srebro, U.; Yakubov, E. (Український математичний вісник, 2010)
We give an exposition of the recent progress in the theory of the Beltrami equations with the degeneration.